Promoting the sulfur conversion kinetics via a solid auxiliary redox couple embedded in the cathode of Li–S batteries. Issue 7 (26th May 2020) - Bizuneh, Girum Girma; Fan, Jingmin; Xu, Pan; Yuan, Ruming; Cao, Lin; Zheng, Mingsen; Dong, Quan-Feng
Abstract : Cobalt phthalocyanine-solid auxiliary redox mediator-embedded graphene, expediting the conversion of polysulfides and activation of Li2 S in Li–S batteries. Abstract : The sluggish kinetics of the sulfur conversion reactions in Li–S batteries is a critical challenge for their application. Thus, many studies have been dedicated to promoting the conversion process by including either functionalized matrix materials in the cathode or redox mediators in the electrolyte. Herein, by embedding a solid auxiliary redox species, we designed and prepared a composite that can be used as a matrix for a sulfur cathode. Differing from the conventional method, in which all the so-called redox mediators utilized are dissolved in the electrolyte, we employed a solid auxiliary redox species, a cobalt phthalocyanine complex supported on graphene structures, as skeleton materials of sulfur to promote the conversion kinetics in Li–S batteries. The graphene–cobalt phthalocyanine hybrid played a prominent role in promoting the kinetics of polysulfide conversion with multiple functions of reducing the activation energy hill, transferring electrons, suppressing the shuttle effect, etc. Consequently, the Li–S battery with the graphene–cobalt phthalocyanine–sulfur cathode showed better electrochemical performance than the battery with the graphene–sulfur cathode. Typically, a high initial capacity of 1400 mA h g −1 was achieved at 0.1C during the initial activation cycle, and the 1 st and 300 th cycle capacities at 0.5C were 1116 and 860 mA h g −1, respectively. Additionally, at a rate of 0.3C, high capacities of 1182 and 869 mA h g −1 were obtained during the 1 st and 500 th cycles, respectively. Furthermore, enhanced rate capability was achieved, delivering a capacity of 874 mA h g −1 at a rate of 2C.